EVALUASI KEBIJAKAN PELAYANAN KEFARMASIAN DI PUSAT KESEHATAN MASYARAKAT TINOMBO KECAMATAN TINOMBO KABUPATEN PARIGI MOUTONG - Uga, Devi Artini (Katalogis, 2018)
This study aims to describe, analyze and menginterprestasikan Evaluation Policy Pharmaceutical Services At Tinombo Community Health Center Tinombo District Parigi Moutong. The research method used is qualitative descriptive research method and data collection technique by observation, interview, and documentation. With the technique of selecting informants by purposive counted 5 people. Research on the Evaluation of Pharmaceutical Service Policy at Tinombo Community Health Center Tinombo District Parigi Moutong Regency uses William Dunn's policy evaluation model, consisting of Effectiveness, Efficiency, Adequacy, Alignment, Responsiveness, and Accuracy. The results of the research have not optimum results, which influenced, among others: 1) the effectiveness aspect is not optimal, 2) the efficiency aspect is good, 3) the sufficiency aspect is good, 4) the aspect of the smoothing is not good, 5) the aspect of responsiveness is optimal, 6) the aspect of precision is good.